THE CONTRIBUTION OF STUDY HABITS AND INTERESTS TO THE LEARNING OUTCOMES OF THE SUBJECTS OF THE QUR'AN HADITH STUDENTS OF CLASS VIII MTS MESRA PEMATANGSIANTAR CITY, T.A 2017/2018 - Reny Yuliana (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2019)
This study aims to find out: (1) contribution positive anda significancebetween student learning habits towards learning outcomes, (2)contribution positive anda significance between students' interest inlearning on the results of learning, and (3) contribution positive anda significance between learning habits and student learning interest towards learning outcomes. The research was conducted at MTs MesraPematangsiantar city. This type of research is quantitative with acorrelational method. The population in the study were all eighth gradestudents in the MTs Mesra Pematangsiantar city, amounting to 89 people,while the sample amounted to 72 students using the Krejcie Morgan table.Data analysis techniques used simple correlation and correlation analysiswith a significant level α = 0.05. The results of the study are: (1) there arepositive and significant contributions to learning habits with learningoutcomes ini MTs Mesra Pematangsiantar city, (2) there is a positive andsignificant contribution between interest in learning with the results oflearning in MTs Mesra Pematangsiantar City., and (3) there are positiveand significant contributions together between learning habits and interestin learning with Al-learning outcomes ini MTs Mesra Pematangsiantarcity.